Multi-choice goal programming model for optimal financial resources in Islamic bank - Karmila Hanim Kamil,; Abdul Ghafar Ismail,; Shahida Shahimi,; Zaidi Isa, (Penerbit Universiti Kebangsaan Malaysia, 2020)
As the primary operational tool in the Islamic economics system, Islamic banking is assumed to run on the broader perspective of multi-dimensional objectives based on the foundation of shariah principles. This paper explicitly develops a multi-choice goal programming (MCGP) model of an Islamic bank for the optimal allocations of financial resources that satisfy both economic and social goals. The optimization model is verified using data from one of the premier Islamic banks in Malaysia as a sample model in determining the patterns and strategies taken in the allocations of financial resources. The veracity of the model is tested in terms of its ability to meet the specified target goals with minimum total deviations and to project the optimum allocation of asset and liability composition for a one-year time horizon. Results showed that the model could generate optimal financial resources that meet the specified target goals for economic and social objectives. A simulation analysis has been successfully performed to see the impact of changing the priority weight of management goals on the composition of financial resources. Thus, the model would be beneficial to the policymakers at Islamic banks for decision support and planning in view of its ability to incorporate economic and social objectives. Additionally, the proposed MCGP model offers flexibility to decision-makers in setting management target goals in the form of interval values to avoid error estimation of the decision.